Optical characterization of dissolved organic matter in Kuroshio-Oyashio confluence region: Implication for water mass mixing. (July 2022) - Wang, Yasong; Wang, Yinghui; Ge, Huangmin; Liu, Bilin; Wu, Jianqiang; Han, Lulu; Liu, Yongsheng; Yu, Jianchun; Xu, Yunping
Abstract: Chromophoric dissolved organic matter (CDOM) and fluorescent DOM (FDOM) are important components of DOM and play many important roles in biogeochemical processes. Here, we examined the concentration, composition, and distribution of DOM in waters (0–1000 m depth) from the Kuroshio-Oyashio confluence region (Northwestern Pacific), a key area for ocean carbon cycle and an important fishery. Dissolved organic carbon concentration varied between 30.5 and 78.2 μmol L −1 with a higher level in surface waters. Two humic-like components (C1, C3) and one protein-like component (C2) were identified by fluorescence excitation emission matrices-parallel factor analysis. The C1 and C3 intensity generally increased with depth, and positively correlated with apparent oxygen utilization ( p  < 0.01), whereas the C2 intensity decreased downward, and negatively correlated with apparent oxygen utilization ( p  < 0.01), suggesting in-situ production of bio-refractory C1 and C3 during the microbial transformation of labile organic matter (like C2). The C1 intensity was significantly different among three water masses (p < 0.01) that was 11.7 ± 2.5 × 10 −3 R.U. for Kuroshio Current, 20.1 ± 1.9 × 10 −3 R.U. for Oyashio Current, and 26.1 ± 5.8 × 10 −3 R.U. for North Pacific Intermediate Water. The application of three-endmember mixing model based on the C1 intensity and salinity revealed variable contributions of Kuroshio, Oyashio, and North Pacific Intermediate Water that were consistent with the predication from water temperature and salinity. Our study suggests that the optical property of DOM is a useful tracer for water masses in the Kuroshio-Oyashio confluence region, consisting with previous reports for other marine environments. Highlights: Opposite trends were found for vertical profiles of waterDOM and CDOM concentrations. Humic-like fluorescence C1 is the most sensitive optical tracer for different water masses. Contributions of Kuroshio, Oyashio and North Pacific Intermediate Water were quantified.